Antiradical Activity of Andaliman (Zanthoxylumachanthopodium DC) Fruit Extract - Edi Suryanto; H. Sastrohamidjojo; Sri Raharjo (Indonesian Food and Nutrition Progress, 2004)
Andaliman (Zanthoxylum achanthopo-dium DC) was evaluated as a potential source of phenolic antioxidant compounds. Phenolic compounds were obtained from andaliman fruits by sequential extraction using hexane, acetone and ethanol to obtain three separate fractions. In this study, the antioxidant properties of andaliman at 10 different concentrations and common food additives of BHT at 200 ppm and α-tocopherol at 1000 ppm were compared. The antioxidant properties of andaliman fruits extracts were evaluated using 1,1-diphenyl-2-picrylhdrazyl (DPPH) radical decoloration test. The ethanol extract consistently showed higher activity than hexane and acetone extracts in DPPH radical scavenging whereas BHT as synthetic antioxidant had weaker radical scavenging activity. The α-tocopherol as positive control showed similar antiradical activity with ethanol extract at 500 ppm in DPPH system. The addition of ethanol extract at concentration of 900 and 1000 ppm, exhibited excellent antiradical activities and its efficacy was higher than that of 200 ppm BHT and 1000 ppm α-tocopherol in DPPH radical. It is concluded that the three andaliman fruit extracts had antiradical activities in the DPPH radical decoloration test.